Communication, information, and education (CIE) on food safety issues in Kalimojosari Village, Pekalongan - Muthoharoh, Ainun; Waznah, Urmatul; Slamet, Slamet; Rahmasari, Khusna Santika; Nur, Achmad Vandian (Community Empowerment, 2021)
Food safety issues in Indonesia are still a common concern. Lack of knowledge causes the number of food safety cases is increasing, such as snack poisoning and diarrhea. This community service was carried out to form the PKK Food Safety Cadre in Kalimojosari Village which is expected to provide information and education to local residents regarding food safety. The implementation method applied was communication, information, and education counseling through the lecture method. The result of this community service activity is an increase in knowledge about food safety issues by 6.08%.